Bismuth Electrocatalyst Enabling Reversible Redox Kinetics of a Chelated Chromium Flow Battery Anolyte. Issue 3 (1st March 2022) - Proctor, Aaron D.; Robb, Brian H.; Saraidaridis, James D.; Marshak, Michael P.
Abstract : Metal electrocatalysts have been reported to improve the electron transfer kinetics of aqueous redox flow battery electrolytes on various types of carbon electrodes. In this work, we electrodeposited bismuth metal onto a carbon paper anode of a redox flow battery containing our previously reported polyaminocarboxylate-chelated chromium electrolyte. Depositing 0.58 mg cm –2 of bismuth metal enabled an electrochemically reversible electron transfer for the Cr(II)/Cr(III) couple, resulting in a 3.9% voltage efficiency increase over ten cycles at 100 mA cm –2 across an 80% state of charge window, while maintaining >99% current efficiency. The bismuth electrocatalyst provided other improvements, such as a 13% increase in average discharge power density when cycling at 80% energy efficiency, along with a 60% decrease in charge transfer resistance and 12% decrease in the full cell area specific resistance. A chelated bismuth complex was also utilized as a bismuth source for electrodeposition, providing an example of how polyaminocarboxylate ligands can be further implemented into efforts towards improving the energy efficiency of aqueous redox flow batteries.